Non-spatial and spatial characteristics of international tourists' behaviour in Melaka World Heritage Site - Nurul Diyana Md. Khairi, 1988-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2017